The impact of the grassland ecological compensation policy on the modernization of grassland animal husbandry: evidence from Inner Mongolia - Mei Yong; Lili Xu; Chen Xue; Fulin Du (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgainst the background of China’s modernization, which emphasizes harmonious coexistence between humans and nature, it is highly important to explore whether the grassland ecological compensation policy (GECP) can protect grassland ecosystems while promoting the modernization of grassland animal husbandry and whether it has spillover effects on rural revitalization.MethodsOn the basis of survey data from 475 herding households in Inner Mongolia, this study constructs an index system for the modernization of grassland animal husbandry, measures the level of modernization via factor analysis, and analyzes the impact of the GECP on the modernization of grassland animal husbandry.Results and discussionThe conclusions are as follows: (1) Through ordinary least squares regression (OLS) and moderation effect models, the GECP can significantly promote the modernization level of grassland animal husbandry. For every 1% increase in the compensation amount, the level of modernization increases by 2.355%. The scale of livestock breeding positively moderates this relationship, with larger scales amplifying the policy’s effect. (2) Threshold effect analysis reveals a dual-threshold effect on the basis of the compensation amount and grassland area. The relationship between the policy and modernization changes significantly as the threshold values vary. The dual-threshold values for the compensation amount are 6,450 and 11,517, and those for the grassland area are 279 and 4,900. (3) Heterogeneity analysis reveals that for households that practice captive breeding, a 1% increase in compensation increases the modernization level by 2.927%, whereas no significant impact is observed for households that practice year-round grazing.